MoVAL, a new approach to software architecture and its comparison with existing views based approaches in software engineering - Kheir, Ahmad; Naja, Hala; Oussalah, Mourad (INFOCOMP Journal of Computer Science, 2014)
Views and viewpoints are concepts usually adopted in an important number of works in software engineering in different domains, like in requirements specification, system modeling, system implementation, and mainly in software architectures. This paper presents a survey about the use of viewpoints in these different domains, and leads a comparative synthesis between different approaches in order to induce their limitations. Also, it briefly presents the main characteristics of our views based approach MoVAL that solves two kinds of problems during view-based software development: the stakeholders' communication complexity and the lack of an architecture definition process guiding architect during architecture construction.